Ispitivanje o predviđanju prognoze bolesnika s akutnim neuspjehom jetre liječenim umjetnim jetrom seruma NLR i IL-6 izrazom - Liu, Xiaojing; Xu, Juan; Du, Fenjing; Yang, Xin; Hou, Jintao; Fan, Yan (Journal of Medical Biochemistry, 2025)
Objective To observe the relationship between the expression of serum interleukin-6 (IL-6) and neutrophil/lymphocyte ratio (NLR) and the prognosis of patients with acute liver failure (ALF) treated with artificial liver. Methods 80 patients with ALF from January 2021 to October 2023 were included. All of them received artificial liver system treatment. All of the included subjects completed the effective follow-up for three months. The patients were followed up until April 30, 2023. According to the disease outcomes of patients after the end of follow-up, they were divided into survival group and death group. The serum IL-6 and NLR expressions of the two groups were compared, and the relationship between serum IL-6 and NLR expressions and the prognosis of patients with ALF treated with artificial liver was analyzed. Results At the end of follow-up of 80 patients with ALF, 50 patients survived, with the survival rate of 62.50%; 30 patients died of illness, with the mortality rate of 37.50%. Comparing the general data between the two groups (P>0.05). The expression levels of serum IL-6 and NLR in the death group were higher (P<0.05). The Logistic regression model was built to obtain the equation: y=-9.007+0.106 (IL-6) +0.995 (NLR), the high expressions of serum IL-6 and NLR might be a risk factor for the increased risk of death in patients with ALF after treatment (P<0.05). The receiver operating characteristic (ROC) curve indicated that the area under curve (AUC) of fasting serum IL-6 and NLR expressions in patients with ALF predicting the prognosis of artificial liver treatment were 0.727 and 0.789. When the AUC of serum IL-6 combined with NLR predicting the prognosis of artificial liver treatment in patients with ALF was 0.889, the predictive values were ideal. Conclusion The expression of serum IL-6 and NLR is correlated with the prognosis of patients with ALF treated with artificial liver. The high expression of serum IL-6 and NLR may be a risk factor for the increased risk of death in patients with ALF after treatment. Clinical intervention can be given to patients with high expression of serum IL-6 and NLR, so as to correct the abnormal expression of serum IL-6 and NLR, and reduce the mortality risk of patients after artificial liver treatment.